Reef Fish Community Condition in The Adjacent Waters of Ternate Island - Utama, Rizkie Satriya; Edrus, Isa Nagib; Makatipu, Petrus Christianus (Oseanologi dan Limnologi di Indonesia, 2019)
Coastal development of North Molluccas put concern to coral reefs and reef fishes to be a vital regional asset and also a vurnarable consequence toward the development effects. A method used was underwater visual cencus on the permanent belt transect. The selected indicator monitoring used were eight families of reef fishes. Results showed that there were 108 species of reef fishes identified, consist of  31 species indicator fishes of corallivore, 45 species herbivorous fishes and 32 species carnivorous fishes (based on punctuation group). Density means of a corallivorous group is 1,598 ± 283 individual/ha, a herbivorous group is 4,751 ± 1.034 individual/ha, and a carnivorous group is 890 ± 622 ekor/ha, respectively. A mean of reef fish stocks is 420 ± 162 kg/ha that consist of 320 ± 130 kg/ha for herbivorous fishes and  group and 100 ± 64 kg/ha for carnivorous fishes. Indicator fish dominance were attained by Chaetodon kleinii, Chaetodon lunulatus,  Chaetodon baronessa, Heniochus varius, Chaetodon melannotus, Chaetodon trifascialis, and Chaetodon octofasciatus. Herbivorous fishes (84%) more dominat than  carnivorous (16%) in terms of individual composition. Dominant species of herbivorous fishes included Ctenochaetus striatus, Ctenochaetus binotatus, Zebrasoma scopas, Scarus ghobban, Lutjanus biguttatus, Acanthurus pyroferus, Chlorurus sordidus, Chlorurus bleekeri, Siganus vulpinus, and Scarus dimidiatus. The one of carnivorous fishes dominated was only Lutjanus biguttatus. Increasing trend of species numbers and density for corallivorous, herbivorous and carnivorous fishes occured during 2015 and 2017 in majority of study sites. Contrarily, the biomass values not increased in majority of the sampling sites.